The White Prophet, Volume 1 (of 2) - Caine, Hall, Sir, 1853-1931; Woodville, Richard Caton, 1856-1927 (Salt Lake City, UT : Project Gutenberg, 2016)
"The White Prophet, Volume 1" by Sir Hall Caine is a novel written in the early 20th century. The narrative is set against the backdrop of British rule in Egypt, illustrating the complex cultural and political tensions of the era. At the center of the story is Gordon Lord, a British officer, who finds himself entangled in the struggles between the native Egyptians and their British rulers, particularly focusing on the rise of a charismatic new leader named Ishmael Ameer. At the start of the novel, a sham battle staged by British officers in Cairo escalates tensions between British forces and the local population, igniting feelings of resentment among the Cairenes. Amid this backdrop, Lord Gordon, who is depicted as empathetic toward the locals and proud of his Egyptian heritage, becomes concerned about a potential uprising incited by Ishmael Ameer, a preacher stirring discontent among the people. As Gordon prepares to undertake a mission to arrest Ameer, he grapples with his duty to the British Crown and his personal conviction, setting the stage for a deeper exploration of identity, loyalty, and the implications of colonialism in Egypt. (This is an automatically generated summary.)
Release date is 2016-06-15
Produced by Al Haines
Keywords: British -- Egypt -- Fiction; Egypt -- Fiction